Effect of after-meal sucrose-free gum-chewing on clinical caries $jSzoke, J. Banoczy, H.M. Proskin. - Szoke, J.; Banoczy, J.; Proskin, H.M.
Previous in situ and in vitro studies have demonstrated that the chewing of sucrose-free gun after eating reduces the developments of dental caries. To investigate the extrapolation of these finding to the clinical setting, we conducted a two-year study on 547 schoolchildren in Budapest, Hungary. Subjects in the "Gum" group were instructed to chew one stick of a commercially available sorbitol-sweetened chewing gum for 20 minutes after meals, three times daily. The "Control" group was not provided with chewing gum. After two-years, the "Gum" group exhibited a 38.7% reduction in incremental caries, excluding white spots, compared with the "Control" group. Including white spots, a corresponding 33.1% reductions was indicated. These results clearly suggest that even in a moderate caries population practicing normal oral hygiene, including the use of fluoride dentrifices, an after-meal gum-chewing regimen can significantly reduce the rate of caries development.
Keywords: Chewing gum; Caries clinical trial